From Supervision to Filtering: Parental Monitoring and Regulatory Practices in Children’s Digital Use - Saharudin, Saharudin; Putri, Regita Riani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This qualitative study examines parental monitoring and regulatory practices concerning the everyday family contexts of young children’s digital media usage. Method: Using a qualitative case study design, data collection involved semi-structured interviews with parents of young children, which were analysed using thematic analysis. Results: The findings reveal that parental monitoring operates as a layered and progressive process rather than a singular strategy. Three interrelated dimensions emerged: presence-based monitoring, activity inspection practices, and content restriction and digital filtering. Presence-based monitoring was enacted through physical supervision and real-time accompaniment during children’s digital engagement. Activity inspection involved reviewing digital traces such as viewing histories and application usage to evaluate appropriateness and interests. Content restriction was implemented through time limits, password protection, parental control applications, account blocking, and curated content selection. These practices demonstrate how parents operate as digital gatekeepers who both shape and control children’s digital environments. Novelty: The study contributes to the digital parenting by theorizing monitoring as a continuum that ranges from embodied supervision to trace-based inspection and system-based control. The findings highlight the relational and structural aspects of parental authority in digitally mediated childhood. It also underscores the need for a contextualized understanding of digital governance within families.